African seed enterprises : sowing the seeds of food security - Mele, Paul van; Bentley, Jeffery W. (Jeffery Westwood), 1955-; Guéi, Robert G. (Published by the Food and Agriculture Organization of the United Nations and the Africa Rice Center by arrangement with CAB International, 2011)
In most developing countries, good quality seed is hard to obtain and farmers struggle to save seed from one year to the next. This title takes a people-centred look at the companies, public agencies and family farms that are taking on this role and making a difference to food security across Africa.